Safety of Lumbar Interbody Fusion Procedures for Degenerative Disc Disease: A Systematic Review With Network Meta-Analysis of Prospective Studies. Issue 5 (June 2021) - Chi, Kuan-Yu; Cheng, Shih-Hao; Kuo, Yu-Kai; Lin, En-Yuan; Kang, Yi-No
Study Design: A network meta-analysis. Objectives: Lumbar degenerative disc disease (LDDD) is an important issue in aging population, for which lumbar interbody fusion (LIF) is a feasible management in cases refractory to conservative therapy. There are various techniques available to perform LIF, including posterior (PLIF), transforaminal (TLIF), and anterior (ALIF) approaches. However, the comparative safety profile of these procedures remains controversial. Our study aimed to evaluate comparative adverse events of the LIF procedures in patients with LDDD. Methods: We searched 5 databases for relevant prospective cohort studies and randomized clinical trials. After quality assessments, we extracted neural, spinal, vascular, and wound events for conducting contrast-based network meta-analysis. Results were reported in risk ratio (RR), 95% confidence interval (CI), and surface under the cumulative ranking (SUCRA). Results: We identified 14 studies involving 921 participants with LDDD. Pooled result showed that open PLIF (OPLIF) leads to significantly higher overall adverse event rate than does open TLIF (OTLIF; RR = 3.43, 95% CI = 1.21-9.73). OTLIF confers the highest SUCRA in neural (78.7) and spinal (80.8) event rates. Minimally invasive TLIF has the highest SUCRA in vascular event (84.2), and minimally invasive PLIF has the highest SUCRA in wound event (88.1). No inconsistency or publication bias was detected in the results. Conclusions: Based on our results, perhaps OPLIF should be avoided in the management of LDDD due to the inferiority of overall complications. Specifically, TLIF seems to have the safest profile in terms of neural, spinal, and vascular events. Nevertheless, shared decision making is still mandatory when choosing the proper LIF procedure for patients with LDDD in clinical practice.